Narrative preaching: theory and praxis of a new way of preaching - Johan Janse van Rensburg (Acta Theologica)
From text: Perhaps the title is misleading. It may create the impression that narrative preaching is a never-before-discovered new method of communicating the gospel of salvation. Of course, stories have been used in sermons for a very long time. Narrative preaching as an art form is in itself a much-discussed and -published theme in the field of homiletics. Yet, in many ways, it is new. Compared to other forms of preaching such as expository preaching, thematic preaching and the homily, the narrative sermon is less used. As such, it does represent a new way of preaching for many. Furthermore, it is also new because it is only now receiving the attention it deserves in the South African context, and particularly in the Dutch Reformed Church. While narrative preaching has been acknowledged in academic circles for some time, a handful of preachers have only recently become aware of the many possibilities of this form of preaching.